Validity of flow chart for vaginal discharge in pregnant women - Menezes, Maria Luiza B.; Faúndes, Aníbal E. (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction:the Health’s Ministry of Brazil recommends syndromic approach to manage people with STD, nevertheless, does not have registeredthe validation of flow chart of vaginal discharge in Brazilian pregnant women. Objective:analyze validation of flow chart for vaginal dischargerecommended by Health’s Ministry of Brazil in 400 pregnant women from pre-natal service at Centro Integrado de Saúde Amaury de Medeiros,Recife – PE, in the period from January to July of 2002. Methods:the design of the study was validation of diagnostic test. The pregnant womenwere submitted to gynecologic exam, whiff test, collection of vaginal fluid to microscopic fresh exam and Gram coloration and urine collection toresearch Chlamydia trachomatisand Neisseria gonorrhoeaeby molecular biology technique. It was researched the validation of vaginal dischargeflow chart for the diagnostic of cervicitis and vaginal infections throuh sensibility, specificity, positive and negative preditive value and Youden’sindice. Results:values of sensibility, specificity, positive and negative preditive value, positive and negative verossimilhance ratio , accuracy andYouden’s indice of flow chart for vaginal discharge to cervicitis, tricomoniasis, bacterial vaginosis and candidiasis changed, respectively, from 26%to 95%; 42% to 92%; 16% to 72%; 39% to 99%; and 0,0 to 0,6; according with the part of flow chart used. Conclusion: the flow chart showed weakfor cervicitis; very good validation for candidiasis, trichomoniasis and bacterial vaginose when uses microscopy; regular bacterial vaginose, but weakfor trichomoniasis, when uses criterion of association of vaginal smear and whiff test; and tolerable for trichomoniasis and weak for bacterial vagino-se and candidiasis when uses only the criterion of vaginal discharge.